Laboratory evaluation of crude wood vinegar as a potential anti-mould chemical for Sesendok and Jelutong - Lee, Yan Yi (2018)
Sesendok and Jelutong have good potential to replace rubberwood as their fast growth rate are similar to rubberwood. But the durability of the Sesendok and Jelutong are very low. The durability of Sesendok and Jelutong have been ensured and classified as non-durable wood species under exposed condition. Sesendok and Jelutong are easily attacked by sapstain and mould fungi especially under exposed condition. Endospermum spp. (Sesendok) and Dyera costulata (Jelutong) were used in this study. The mould fungi coverage and wettability were tested in different concentration of wood vinegar in non-volatile and volatile state. Based on the result obtained, there was a significant difference in the concentration of wood vinegar towards the mould fungi coverage on Sesendok and Jelutong (p<0.05). In fact, there was no significant difference between volatile and non-volatile wood vinegar treatment on Sesendok and Jelutong. Generally, the most optimum concentration of wood vinegar to function as antistain chemical for Sesendok and Jelutong is 1:1 and undilute. Both Sesendok and Jelutong treated with 1:1 concentration and undilute concentration wood vinegar had successfully inhibited from mould fungi attack. Generally, there is no significant relation between discoloration and wettability (p<0.05).